Tradisi Ngejot Jerimpen Galungan Di Desa Adat Nyitdah Kecamatan Kediri Kabupaten Tabanan - Ni Made Ayu Erna Tanu Ria Sari (Purwadita : Jurnal Agama dan Budaya, 2022)
The meaning of Ngejot Jerimpen Galungan is besides being a symbol of sharing happiness, it is also a symbol of congratulations and prayers for the newlywed couple in their new life. Positive impact For the newlyweds they feel accepted as new members in the community and the community is also happy to welcome the newlyweds to become members of the new community and the community also congratulates the newlyweds on their new life. The Niskala (unreal) impact of the Ngejot Jerimpen Galungan Tradition is that if one of the newlyweds from the Nyitdah Traditional Village community does not carry out this tradition, it is believed that the newlyweds in living a married life will not get physical and spiritual happiness. Keywords: Keywords: ngejot, galungan, traditional village